HOW NEW MARKETING STRATEGIES APPLIED BY FAST-FOOD RESTAURANTS IN TASHKENT AFFECT GEN-Z’S PERCEPTION OF THE BRAND (American Journal of Pedagogical and Educational Research, 2025)
Fast-food consumption in Tashkent has increased rapidly in recent years, leading to stronger competition among both local and international fast-food brands. As a result, restaurants have started to rely more on modern marketing strategies such as social media advertising, influencer promotions, and discount-based campaigns to attract young consumers. This study examines how these marketing strategies affect Gen-Z’s perception of fast-food brands and their purchasing decisions in Tashkent.The research is based on a quantitative survey conducted among 100 respondents aged 16–25. The findings show that the most popular fast-food restaurants are “Evos” (35%), “KFC” (21%), “Max Way” (14%), and “Oq Tepa Lavash” (10%), with an average spending of approximately 65,000 UZS per visit. The results indicate that promotions and discounts have the strongest influence on brand choice, followed by location convenience and brand reputation. While social media and influencer marketing increase brand awareness, they do not significantly affect purchasing frequency in the short term. Overall, the study suggests that Gen-Z consumers in Tashkent remain highly price-sensitive and tend to make rational, value-oriented decisions when choosing fast-food brands.